Analisis Efektivitas Iklan Melalui Media Sosial Tiktok di UMKM Jamu Mitra Sehat - Siwitri Munambar; Fitria Naimatu Sadiyah; Rosiana Nurfitri (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
The purpose of this research was to determine the effectiveness of advertising for the MSME product Jamu Mitra Sehat using the social media platform TikTok. The method used in this study was descriptive quantitative using the EPIC model. The data analysis tool utilized was Microsoft Excel. The results of the analysis indicated that the effectiveness of advertising conducted through TikTok social media using the EPIC model in each dimension fell within an effective range. The communication dimension received the highest average score compared to other dimensions, which was 4.20. The persuasion dimension obtained an average score of 4.19, while the empathy dimension received an average score of 4.10. The impact dimension had the lowest average score compared to the other three dimensions, with a score of 4.02. Overall, the analysis of advertising effectiveness across each dimension calculated using the EPIC Rate yielded a score of 4.13, indicating that the analysis of effectiveness was deemed effective